Corporal Punishment: National Trends, Longer-Term Consequences, and Parental Perceptions of Physical Discipline - Fréchette, Sabrina (Université d'Ottawa / University of Ottawa, 2016)
Corporal punishment is a controversial form of discipline. To inform the debate on corporal punishment, one of the objectives of the current dissertation was to characterize parental use of this disciplinary strategy and to examine its long-term developmental outcomes. The dissertation drew on data from the National Longitudinal Survey of Children and Youth (NLSCY) to understand potential social change in corporal punishment and to characterize parents who continue to use this strategy. Over a 14-year period (1994-1995 to 2008-2009), results revealed a significant decrease in the use of corporal punishment and other negative strategies (e.g., psychological aggression), as well as a significant increase in the use of positive strategies (e.g., reward/praise and explain/teach). Nevertheless, approximately 25% of Canadian parents still use corporal punishment with children aged 2–11 years; therefore, it remains an issue that merits continued attention. While several socio-demographic factors significantly distinguished parents who use corporal punishment, other more dynamic variables may be important to consider, such as parental stress and their attitudes toward corporal punishment. For the outcomes associated with corporal punishment, NLSCY data revealed that experiences of corporal punishment at 2-3 years are associated with increased externalizing behaviours at 8-9 years. Results also indicated that, within a certain disciplinary context (more hostile and punitive parenting), early corporal punishment is associated with increased externalizing behaviours at 14-15 years, increased internalizing behaviours at 8-9 and 14-15 years, and reduced prosocial behaviours at 8-9 and 14-15 years. Overall, results confirmed that corporal punishment represents a small but non-trivial risk factor for child development. The second objective of the current dissertation was to address one of the central limitations of the existing literature on corporal punishment by clarifying what parents self-label as corporal punishment. Using a sample of 338 Canadian caregivers, the study assessed the relation between responses to a general question on corporal punishment and responses to questions on specific physical disciplinary strategies. Predictors (e.g., cultural norms, attitudes toward and childhood experiences of corporal punishment) of this relation were then investigated. Results suggested that questions such as the one used in the NLSCY may reflect parental use of milder forms of corporal punishment. Results also revealed that some caregivers remain undetected by general questions on corporal punishment. Factors such as attitudes toward corporal punishment can help identify those caregivers who use physically punitive strategies but who do not endorse corporal punishment. Results from the current dissertation offers support for the anti-corporal punishment perspective and calls for the de-legitimatization of this disciplinary strategy across society.
Keywords: corporal punishment; discipline; prevalence; developmental outcomes